Redescription of Herdmania papietensis Herdman, 1882 (Ascidiacea, Pyuridae) from Polynesia - Monniot, Françoise; Debitus, Cecile (Zootaxa, 2015)
Among the Pyuridae family the genus Herdmania Lahille, 1888 differs from the diagnose of Pyura Molina, 1782 by the presence of needle-shape echinated spicules in all tissues. These striking elements formerly led to identify many specimens collected in tropical or temperate waters as Herdmania momus (Savigny, 1916). Later the genus was split into several species with a special attention to the different structure of the gonoducts. Newly collected specimens and a revision of previously described animals in Polynesia lead to the redescription of Herdmania papietensis Herdman 1882 from Polynesia and to compare it to the other Herdmania species known in the Pacific Ocean.